News Shocks and Asset Price Volatility in General Equilibrium - Akito Matsumoto; Pietro Cova; Massimiliano Pisani; Alessandro Rebucci (Inter-American Development Bank (IDB), 2011)
This paper studies equity price volatility in general equilibrium with news shocks about future productivity and monetary policy. As West (1998) shows, in a partial equilibrium present discounted value model, news about the future cash flow reduces asset price volatility. This paper shows that introducing news shocks in canonical dynamic stochastic general equilibrium model may not reduce asset price volatility under plausible parameter assumptions. This is because, in general equilibrium, the asset cash flow itself may be affected by the introduction of new shocks. In addition, it is shown that neglecting to account for policy news shocks (e. g. , policy announcements) can potentially bias empirical estimates of the impact of monetary policy shocks on asset prices.
Keywords: E32; F30; F40; G11; 330